Ecological network complexity scales with area - Galiana, Núria; Lurgi, Miguel; Bastazini, Vinicius A. G.; Bosch, Jordi; Cagnolo, Luciano; Cazelles, Kevin; Claramunt-López, Bernat; Emer, Carine [UNESP]; Fortin, Marie-Josée; Grass, Ingo; Hernández-Castellano, Carlos; Jauker, Frank; et al. (Springer Nature, 2022)
Larger geographical areas contain more species—an observation raised to a law in ecology. Less explored is whether biodiversity changes are accompanied by a modification of interaction networks. We use data from 32 spatial interaction networks from different ecosystems to analyse how network structure changes with area. We find that basic community structure descriptors (number of species, links and links per species) increase with area following a power law. Yet, the distribution of links per species varies little with area, indicating that the fundamental organization of interactions within networks is conserved. Our null model analyses suggest that the spatial scaling of network structure is determined by factors beyond species richness and the number of links. We demonstrate that biodiversity–area relationships can be extended from species counts to higher levels of network complexity. Therefore, the consequences of anthropogenic habitat destruction may extend from species loss to wider simplification of natural communities.